S-phase specificity of cell killing by docetaxel (Taxotere) in synchronised HeLa cells. - Hennequin, C. (Nature Publishing Group, 1995)
Cell viability following short (1 h) contact with paclitaxel or docetaxel was assayed using synchronised HeLa cells. Docetaxel proved almost totally lethal against S-phase cells. Its toxicity was only partial against cells in mitosis, and declined to a minimum with progression to G1. For paclitaxel, cytotoxicity increased with progression through S and G2, peaked at the time of mitosis, and decreased thereafter. Maximum resistance to paclitaxel was in early S. Although lethal, brief exposure to docetaxel in S-phase did not delay progression through S and G2. Gross damage was detectable immediately after mitosis, with dysfunction in cytokinesis and accumulation of multinucleated, non-viable cells. Arrest of cells at prometaphase required continuous contact with lethal amounts of docetaxel or reintroduction of drug shortly before mitosis following pulse-chase treatment in mid-S-phase. Paclitaxel at moderate doses presumably acts mostly via damage to the mitotic spindle. In contrast, the available data suggest that docetaxel primarily targets centrosome organisation, leading to abortive mitosis and cell death.